A mobilidade do trabalho no contexto do gerenciamento de projetos e competências inerentes - Pereira, Sirlei de Almeida (2017)
Mobile information technologies constantly change the way people communicate, interact and collaborate. The progress and increasing use of these technologies, enable the mobility, and allow organizations to consider the use of geographically dispersed teams that interact at distance, share, exchange, and access the information, everywhere, at any time, remotely, virtually, enabling the work flexibility. Specifically on project-based organizations, this context also modifies the communication, and collaboration processes among professionals who, in particular, have constant interactions with many people, near or far. During these interactions, the work mobility in the projects environment invariably influences the activities, and may emphasizes certain competencies required to project managers who choose to flexibilize their workplace. Considering this context, this study investigated how work mobility has influenced project management, and the skills required for mobile project managers, and sought to understand the subjectivities in the relationships between these phenomena. Mixed methods, qualitative and quantitative, were adopted as data collection procedures, as following: a) in-depth interviews, with 8 specialists, responsible for project management; and b) questionnaire, with 114 project managers. The data were analyzed based on evidence triangulation, and pattern combination. The results indicate that work mobility is intrinsic, and conducive on project management context, and emphasizes commitment, professional maturity, previous experience in project management, and the ability to use mobile information technologies, as a vital part of the skills that must be in evidence for project managers working remotely. In addition, the study presents an integrated framework that consolidates the categories, and particular elements of work mobility on the project management context, constituting, in theoretical terms, the enrichment of the conceptual basis that interrelates the research pillars, and in practical terms, becomes an important benchmark for administrators seeking to achieve the best benefit of work mobility on their project-based environments